Human Resource Information System of Monitoring Employee Attendance Using Microsoft Power BI at Catholic University of De La Salle Manado - Palulungan, Josep (Manajemen dan Kewirausahaan, 2024)
The purpose of this research is to determine the level of usage of attendance devices to further perform the descriptive result and give recommendations to the organization or management on how to improve human resource data. This research was carried out using Microsoft Excel software to collect and process data and then will be analyzed using Microsoft Power BI to visualize the data. Data was collected from Biro Pengembangan Sumber Daya Manusia (BPSDM) at the Catholic University of De La Salle Manado. Employee awareness of using the attendance device at the Catholic University of De La Salle Manado in the mean is significantly low. Based on the data provided, the low level of the mean does not represent personal awareness, considering the maximum attendance personally is 100% and the minimum attendance is 0%. This range could impact the mean significantly, so, the result in this research is the mean of all employees, not personally. Based on the result of this research, it is recommended for the management of the Catholic University of De La Salle Manado to perform a seminar or focus group discussion to explain the importance of using attendance devices, not only for personal financial benefit, but also for human resource management purposes, so employee will use it regardless of any personal financial benefit.